Phase inversion in liquid phase for air-liquid horizontal flow. Issue 1 (1st January 2020) - Edwards, Laura; Ward, Keeran; Chakrabarti, Dhurjati Prasad
Abstract: This project is primarily aimed at determining the effect of phase inversion on oil-water dispersion from a three-phase mixture comprising of an oil-water emulsion at different oil percentages and air at varying liquid and gas flowrates through a horizontal pipe. Parameters affected by phase inversion were investigated such as liquid-side pressure drop, viscosity and flow regimes. The liquid-side pressure drop was estimated and predicted from existing as well as developed correlations. The results obtained were tabulated and represented graphically. Viscosity measurements were taken at different oil percentages. At inversion, the mixture's continuous phase switched from water to oil as indicated by the increase in viscosity and pressure drop. A significant change in pressure drop was noted for all correlations used beyond the point of phase inversion. The viscosity of the liquid phase was tried to be related with oil percentage empirically to get a Reynolds's no of laminar or turbulence. However, that did not influence the prediction significantly. It was also found that tghe occurrence of phase inversion affected the flow regimes of the mixture causing a shift from a plug dominant flow to a more slug-type flow pattern.